Zinc collecting agent GZ-1 and preparation method and application thereof
By developing the new zinc collector GZ-1, the problems of waste of agents and environmental pressure in the process of beneficiation of existing zinc collectors have been solved, and efficient and low-consumable zinc mineral separation and concentrate quality improvement have been achieved.
Patent Information
- Application Number
- CN202510173365.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-17
AI Technical Summary
During the ore dressing process, existing zinc collectors have problems of waste of agents and high environmental pressure, especially when dealing with copper-iron polymetallic ore containing pyrite.
A new zinc collector GZ-1 is developed, which consists of isobutylxenol acrylic acid propylene, isobutylxenol ethyl formate, isobutyl methylthioamide and 2-methyl-1-benz-2-propanol, to improve the capture capacity and selectivity by optimizing the ratio.
GZ-1 zinc collector has high capping ability, has low drug use, good selectivity, alkali resistance or acid resistance, can effectively separate zinc minerals and their convergent minerals, improve the quality of concentrates, and have good environmental protection performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metallurgy and chemical industry, and specifically relates to a zinc collector GZ-1 and a preparation method and application thereof. Background Art
[0002] Copper, lead, zinc and iron minerals usually coexist together in nature. Since copper, lead and zinc minerals have similar physical and chemical properties and coexist densely with gangue minerals such as quartz and feldspar, it is necessary to develop efficient separation processes in the beneficiation process to improve the quality and reduce the impurities of copper, lead and zinc minerals. In recent years, with the development of the economy, the industrial demand for copper, lead and zinc has increased significantly, resulting in a decrease in easy-to-select ores in China and an increase in difficult-to-select multi-metal complex associated ores. In industry, ores with a grade of less than 3% are usually regarded as low-grade ores. Such ores usually contain valuable elements such as sulfur and iron that can be comprehensively recovered. The content and distribution of these elements have a huge impact on the subsequent metal smelting process. For this reason, it is necessary to separate and recover the associated metals in different ways.
[0003] In order to comprehensively utilize copper, lead and zinc ores, priority flotation process, mixed flotation process, equal flotation process and asynchronous flotation process can be adopted. Which process to adopt specifically needs to comprehensively consider factors such as the difference in mineral floatability, mineral properties, process test results and economic benefits, and analyze the effects of different flotation sequences on mineral processing indicators through experiments, so as to determine the optimal flotation recovery process.
[0004] Since the chalcopyrite in the ore is easily oxidized and precipitates copper ions during weathering, which leads to the activation of pyrrhotite and pyrite, the use of xanthate collectors requires "strong pressure and strong pulling", which greatly wastes reagents and directly causes high costs for mineral processing return water treatment and increased environmental pressure. For complex polymetallic ores, especially copper-iron polymetallic ores containing pyrrhotite, it is urgent to develop a zinc collector that can solve the above problems. Summary of the invention
[0005] The first purpose of the present invention is to provide a zinc collector GZ-1; the second purpose is to provide a method for preparing the zinc collector GZ-1; and the third purpose is to provide an application of the zinc collector GZ-1.
[0006] The first object of the present invention is achieved in that the zinc collector GZ-1 is composed of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol.
[0007] The second object of the present invention is achieved by mixing isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol in a prescribed ratio.
[0008] The third object of the present invention is achieved by using the zinc collector GZ-1 in a multi-metal comprehensive utilization and recovery process.
[0009] The zinc collector of the present invention has high collecting capacity, can more effectively separate zinc minerals and their associated minerals from ores, and uses less reagents; has good selectivity, can collect specific minerals, reduce inclusions of other minerals, and improve concentrate quality; has strong alkali resistance or acid resistance, and has wide application conditions; improves the flotation kinetic behavior of fine-particle minerals and increases the flotation speed; has good environmental performance, is easy to biodegrade, and has little pollution to the environment. DETAILED DESCRIPTION
[0010] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.
[0011] The zinc collector GZ-1 of the invention is composed of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol.
[0012] The mass ratio of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol is (0.5-1.5): (0.5-1.5): (0.5-1.5): (0.4-0.6).
[0013] The mass ratio of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol is 1:1:1:0.5.
[0014] The preparation method of the zinc collector GZ-1 of the present invention is to mix isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol in a prescribed proportion to obtain the zinc collector.
[0015] The application of the zinc collector GZ-1 described in the present invention is the application of the zinc collector GZ-1 in a multi-metal comprehensive utilization and recovery process.
[0016] The present invention is further described below with specific implementation cases: Example 1 Weigh 5 kg of isobutyl xanthate propylene ester, 5 kg of isobutyl xanthate ethyl formate, 5 kg of isobutyl methylthiocarbamate and 4 kg of 2-methyl-1-benzyl-2-propanol, and stir and mix to obtain the target zinc collector GZ-1.
[0017] Example 2 Weigh 15 kg of isobutyl xanthate propylene ester, 15 kg of isobutyl xanthate ethyl formate, 15 kg of isobutyl methylthiocarbamate and 6 kg of 2-methyl-1-benzyl-2-propanol, and stir and mix to obtain the target zinc collector GZ-1.
[0018] Example 3 Weigh 12 kg of isobutyl xanthate propylene ester, 15 kg of isobutyl xanthate ethyl formate, 10 kg of isobutyl methylthiocarbamate and 5 kg of 2-methyl-1-benzyl-2-propanol, and stir and mix to obtain the target zinc collector GZ-1.
[0019] Example 4 Weigh 8 kg of isobutyl xanthate propylene ester, 12 kg of isobutyl xanthate ethyl formate, 10 kg of isobutyl methylthiocarbamate and 5 kg of 2-methyl-1-benzyl-2-propanol, and stir and mix to obtain the target zinc collector GZ-1.
[0020] Example 5 Weigh 12 kg of isobutyl xanthate propylene ester, 11 kg of isobutyl xanthate ethyl formate, 12 kg of isobutyl methylthiocarbamate and 6 kg of 2-methyl-1-benzyl-2-propanol, and stir and mix to obtain the target zinc collector GZ-1.
[0021] Example 6 The GZ-1 zinc collector prepared in Example 3 was tested as follows: 1. Sample properties 1.1 Chemical composition and mineral composition Observed with the naked eye, the ores are mostly dark brown and gray-green in color. The mineral aggregates are distributed in an irregular manner, forming a sparse impregnation-like structure of the ore. The results of chemical multi-element analysis of the ore samples are shown in Table 1, and the results of chemical phase analysis of lead, zinc, copper and iron are shown in Tables 2, 3, 4 and 5.
[0022] Table 1 Chemical analysis results of main elements of ore samples / %
[0023] Table 2 Results of phase analysis of lead in raw ore / %
[0024] Table 3 Results of phase analysis of zinc ore / %
[0025] Table 4 Analysis results of copper phase in raw ore / %
[0026] Table 5 Analysis results of iron phase in raw ore / %
[0027] The ore sample is a lead-zinc polymetallic sulfide ore, with the main valuable elements being lead, zinc and iron, with contents of 2.64%, 1.45% and 26.81% respectively, and other associated valuable elements being Au0.10g / t, Ag10.8g / t, Cu0.045%, In55.3g / t and sulfur3.94%. Through observation under a polarizing microscope, X-ray diffraction analysis and MLA analysis, it was found that there were 23 minerals in five categories, including sulfide, oxide, silicate, sulfate and phosphate, in the ore, and the main minerals in the ore were galena, sphalerite, magnetite, pyrite / marcasite, pyrrhotite, black columnar stone, calcium iron pyroxene, iron talc, quartz, calcite and other minerals.
[0028] 1.2 Analysis of the embedding state of main minerals Under the condition of grinding fineness of -0.075mm accounting for 64.39%, MLA was used to measure and count the embedded particle sizes of ore and main target minerals in ore, such as galena, sphalerite, pyrrhotite, pyrite / marcasite, magnetite, hematite / limonite, galena, calcite, andradite, epidote, and talc. The embedded particle sizes of sphalerite, calcite, andradite were the coarsest, with the particle size of +75μm accounting for 33.29%, 38.54% and 31.23% respectively, and their embedded particle sizes were similar to the particle size of ore; followed by galena, pyrrhotite, pyrite / marcasite, magnetite, andradite, andradite, andradite, which were slightly finer than the former, with the particle size of +75μm accounting for 28.17%, 26.98%, 25.16%, 29.55%, 27.37%, and 26.39% respectively.
[0029] 1.3 Symbiotic relationship of main minerals Under the current grinding conditions, the free surface areas of sphalerite, pyrite and pyrrhotite are better, all greater than 91%. The free surface areas of galena, magnetite, hematite / limonite are slightly lower than the former, between 83% and 86%.
[0030] Galena is mainly associated with sphalerite, magnetite, calcite and calcite, with the shared surface area ratios being 3.60%, 1.18%, 2.10% and 1.99 respectively. The free surface area ratio of galena is 86.50%.
[0031] The marmatite is mainly associated with calcite and calcite, with the shared surface area ratios of 1.24% and 1.30% respectively. The free surface area ratio of marmatite is 93.89%.
[0032] Pyrite / marcasite is mainly associated with sphalerite, pyrrhotite and stylosite, with the shared surface area ratios of 1.24%, 1.64% and 1.69% respectively. The free surface area ratio of sphalerite is 91.18%.
[0033] Pyrrhotite is mainly associated with pyrite / marcasite, magnetite, and stylobite, with the shared surface area ratios of 1.05%, 1.45%, and 1.24% respectively. The free surface area ratio of pyrrhotite is 92.54%.
[0034] Magnetite is mainly associated with black lawsonite, hectopyroxene, calcite and talc, with the shared surface area ratios of 4.20%, 2.12%, 1.30% and 1.96% respectively. The free surface area ratio of magnetite is 85.34%.
[0035] 1.4 Distribution characteristics of main minerals The embedded particle size of galena is between 0.001 and 1.37 mm, and the aggregate is granular and dense. It is closely related to sphalerite, magnetite and pyrite, and they are mostly intergrowth or mutually wrapped. Among them, the symbiotic relationship between some galena and magnetite is particularly complex. This part of galena is fine-grained and wrapped in magnetite, and it is not easy to dissociate into monomers.
[0036] The embedded particle size of sphalerite is between 0.005 and 4.75 mm, and it is in an ectomorphic granular form. It is mostly distributed between transparent minerals such as black mandrillite and calcium iron pyroxene, and is partially wrapped in black mandrillite and calcium iron pyroxene, and is partially interbred or wrapped with galena, magnetite, pyrite, and pyrrhotite. Among them, some galena, magnetite, and chalcopyrite are fine-grained or milky and are wrapped in sphalerite, which may partially enter the zinc concentrate and affect the grade of the zinc concentrate.
[0037] The embedded particle size of chalcopyrite is between 0.001 and 1.00 mm, and it is in an angular granular form. It is often associated with sphalerite, galena, pyrite, and pyrrhotite. Some of them are fine-grained and milky and are wrapped in sphalerite; a few are distributed in the form of stars between transparent minerals.
[0038] The embedded grain size of pyrrhotite is between 0.005 and 0.55 mm, and pyrrhotite is in anisotropic shape. It is often interlaced with pyrite, marcasite, magnetite, sphalerite, and galena; some of it is replaced by marcasite and magnetite, and is distributed alternately or mixed with them.
[0039] The particle size of pyrite / marcasite is between 0.005 and 6.00 mm, mostly in euhedral, semi-euhedral and allomorphic shapes. It is mostly scattered and impregnated among transparent minerals such as black mandrillite and calcite; it is often associated with sphalerite, pyrrhotite, galena, etc.; pyrite is partially replaced by marcasite and magnetite, and is mixed with them.
[0040] The embedded particle size of magnetite is between 0.005 and 1.25 mm, and the magnetite is in an allomorphic granular form. It is closely associated with hematite, galena, sphalerite, and pyrite. Some of it is filled between needle-shaped and plate-shaped hematite grains, some of it is interlocked or mutually wrapped with galena, and some of it is simply associated with sphalerite and pyrite; a small amount of magnetite is replaced by hematite, and a small amount of magnetite replaces pyrite.
[0041] 1.5 Analysis of mineralogical factors affecting mineral processing indicators The only carrier minerals for lead in the ore are galena, and the only carrier minerals for zinc are marmatite, both of which are independent sulfide minerals, which are conducive to independent recovery by flotation. Marmatite contains 12.69% Fe, which cannot be removed by physical beneficiation alone. Therefore, the upper limit of the grade of zinc concentrate belongs to grade VI. Most marmatites in the ore are wrapped in fine-grained, milky chalcopyrite, which is difficult to dissociate by grinding and may enter the zinc concentrate, affecting the grade of the zinc concentrate. Some galena and marmatite have a close symbiotic relationship, which may cause marmatite to enter the lead concentrate with galena, affecting the grade of the lead concentrate. There are many types of iron carrier minerals in the ore, among which only magnetite is a useful mineral for iron, and the distribution rate of iron in it is only 12.91%.
[0042] 2. Ore dressing test study According to the results of the ore property study, the valuable minerals in the ore are mainly galena. Sphalerite, chalcopyrite, pyrrhotite, magnetite, and pyrite. Combined with the surface characteristics and magnetism of the above-mentioned minerals, the process flow of mineral recovery mainly includes the combined process flow of magnetic separation followed by flotation and the combined process flow of flotation followed by magnetic separation. Due to the small amount of magnetic separation removal, magnetic separation is placed before lead flotation, and dense dehydration is required before flotation, which increases the complexity of the process. Therefore, the combined process flow of flotation followed by magnetic separation is adopted. The particles with a galena distribution size of <5μm account for 3.72%. This part of fine-grained galena is mostly wrapped in magnetite, which can improve the use of highly selective collectors to pre-enrich the coarse concentrate before grinding, which can prevent the high cost of fine grinding of the original ore and reduce the degree of over-grinding of the target mineral. Due to the variety of recoverable minerals in the ore, the difficulty of the experiment lies in how to fully and efficiently recover various minerals and obtain high-quality concentrates. Since the copper content of the original ore is extremely low, direct priority flotation is not economical, so the principle process flow of copper-lead mixed selection-zinc flotation-sulfur flotation-ferromagnetic selection is initially proposed.
[0043] 2.1 Grinding fineness test The complete dissociation of useful minerals and gangue minerals is an essential prerequisite for the efficient separation and recovery of minerals. Different grinding finenesses are not only related to the dissociation of minerals, but also the appropriate mineral particle size can ensure the high fresh surface activity of minerals, strengthen the full interaction between the mineral surface and the collector, and thus enhance the recovery and separation of minerals. In order to ensure that flotation obtains higher indicators, it is of great significance to determine the grinding fineness in combination with the properties of the ore. Since the ore contains calcite, talc and other gangue minerals that are easy to become muddy, when selecting the appropriate grinding fineness, it is necessary to consider the dissociation degree of useful mineral monomers and to reduce the over-crushing of gangue minerals and deterioration of the flotation pulp environment. Through experiments, it was selected that the grinding fineness of -74μm accounting for 60% is more suitable. At this grinding fineness, when the flotation pulp concentration is 30%, the flotation machine stirring speed is 2000r / min, and the flotation machine inflation volume is 0.4m 3 / h, under natural pH value, different collectors were used to carry out copper and lead collector type tests with a roughing and sweeping process, and the test results are shown in Table 6. As can be seen from Table 6, the five collectors are copper and lead collectors with good selectivity screened out in the early stage. They basically do not collect pyrite at natural pH value, and effectively reduce the test of pyrite inhibitors. When Pa is used alone as a copper and lead collector, the lead grade of the rough concentrate is the highest and the lead and copper recovery rate is the lowest; when Pb-1 and F5B are used in combination, the loss rate of lead in tailings is the lowest, but the loss rate of copper is as high as 52.54%; when 25# black medicine and GTB1 are used in combination, the loss rate of copper in tailings is the lowest, and the recovery rate of lead in the rough concentrate obtained by roughing is the highest. In order to comprehensively recover copper and lead minerals, it is more appropriate to select 25# black medicine and GTB1 in combination.
[0044] Table 6 Grinding fineness test results
[0045] 2.2 Test of copper-lead mixed concentrator regrinding site The rough concentrate obtained from the rough selection of copper and lead is subjected to three-stage selection to improve the quality of the final concentrate. In order to examine the influence of the regrinding location on the recovery of copper and lead, comparative tests were carried out in which the rough concentrate was not ground again, the rough concentrate was regrinded to -0.049mm accounting for 90%, the concentrate 1 was regrinded to -0.049mm accounting for 90%, and the concentrate 2 was regrinded to -0.049mm accounting for 90%, respectively, to examine the feasibility of reducing the copper and lead grade of the middling ore and improve the quality of the copper-lead mixed concentrate. Compared with the rough concentrate not being ground, the rough concentrate can be regrinded to greatly improve the lead grade of the concentrate 1 after the rough concentrate is regrinded. In general, the lead grade of the copper-lead mixed concentrate obtained by the regrinding of the concentrate 2 and the regrinding of the concentrate 3 operation is the highest. The lead grade of the copper-lead mixed concentrate is as follows: regrinding of the concentrate 2 > regrinding of the concentrate 1 > regrinding of the rough concentrate > no grinding. Since the concentrate 3 operation is carried out after the regrinding of the concentrate 2, the lead recovery rate of the copper-lead mixed concentrate is the largest, and it is more appropriate to select the regrinding of the concentrate 1 after comprehensive consideration. The copper-lead mixed concentrate obtained under the regrinding conditions of Selected 1 has a lead grade of 64.85% and a copper grade of 0.91%. Due to the low copper grade, no subsequent copper-lead separation is carried out.
[0046] 2.3 Test on the types of inhibitors for zinc pyrite According to X-ray spectrometry analysis, marmatite contains 53.54% Zn and 12.69% Fe. As the iron content of marmatite increases, its iron ions change its surface properties, affecting the adsorption of the collector on its surface, resulting in a gradual decrease in floatability. The ore contains 1.44% marcasite / pyrite and 2.54% pyrrhotite. Combined with X-ray spectrometry analysis and MLA analysis, it can be seen that the pyrrhotite in the ore is a monoclinic system, and the pyrrhotite contains 60.56% Fe. The floatability of marcasite / pyrite, pyrrhotite, and marmatite gradually decreases. In order to obtain high-quality zinc concentrate, pyrite inhibitors are required to suppress marcasite / pyrite and pyrrhotite. Lime (3000g / t), inorganic depressant LY1 (2000g / t) and organic depressant LY2 (600g / t) were used to test different types of pyrite depressants to examine the effects of different depressants on zinc-sulfur separation. Lime was used as a depressant for marcasite / pyrite and pyrrhotite, and the effect was the best. Through a zinc roughing separation and a zinc scavenging separation, the foam product (zinc rough concentrate and zinc middlings combined) obtained had the highest zinc grade of 29.64%, and the highest zinc recovery rate of 85.39%.
[0047] 2.4 Experiment on selection of zinc collector types Valuable minerals such as pyrite and gangue minerals such as talc in the ore easily react with collectors and interfere with the flotation process. Suitable zinc collectors can not only significantly improve the flotation efficiency of zinc minerals, but also reduce the consumption of reagents. Therefore, suitable zinc collectors are an important prerequisite for achieving efficient and low-consumption flotation processes. The butyl xanthate and ethyl thiocyanate with wide adaptability and strong collection ability were compared with the thiocarbamate collectors A2 and GZ-1 with good selectivity, and the types of zinc collectors were tested to screen the most suitable collectors for this type of high-iron sphalerite. GZ-1 and butyl xanthate were used as collectors. The loss rate of zinc in the tailings was about 2%, but the sulfur recovery rate of the tailings obtained by GZ-1 was higher than that of butyl xanthate, indicating that butyl xanthate has a strong collection ability and collects more pyrite into zinc rough concentrate and zinc middlings; the collection performance of A2 and ethyl thiocyanate is basically similar, and the zinc loss rate and sulfur recovery rate in the tailings are relatively similar. In order to obtain the highest zinc recovery rate and minimize the amount of pyrite entering the zinc concentrate and zinc middlings, GZ-1 is the most suitable choice.
[0048] 2.4 Test on improving quality and reducing impurities of zinc secondary concentrate The results of the beneficiation test on zinc rough concentrate showed that after three beneficiations with the addition of lime, the zinc grade of the concentrate of beneficiation 1 increased from 29.76% to 36.26%, an increase of 6.50 percentage points; after beneficiation 2, the zinc grade of the concentrate of beneficiation 2 increased from 36.26% to 39.12%, an increase of 2.86 percentage points, which was a relatively small increase; after beneficiation 3, the zinc grade of the concentrate of beneficiation 3 (i.e. zinc secondary concentrate) increased from 39.12% to 41.36%, an increase of 2.24 percentage points, which was a relatively small increase. After the fourth beneficiation, the zinc content of the zinc concentrate increased by only 1.5 percentage points, but the zinc loss rate increased significantly, and the zinc grade of the zinc concentrate was difficult to increase to more than 45%. Microscopic examination of the selected 3 concentrate revealed that the sphalerite was in an anisomorphic granular form, most of which were monomer dissociated particles, some sphalerites were wrapped with fine-grained chalcopyrite, and some sphalerites were intergrowth with transparent minerals, pyrrhotite, pyrite, etc.; pyrrhotite was in anisomorphic granular form, most of which were monomer dissociated particles, and some of which were intergrowth with sphalerite, etc.; pyrite was in anisomorphic granular form, mostly intergrowth with sphalerite; chalcopyrite was in anisomorphic granular form, mostly wrapped in sphalerite. The results showed that pyrrhotite and pyrite were the main factors affecting the zinc grade of zinc concentrate. This part of pyrrhotite and pyrite had good floatability, which was difficult to suppress by adding lime, and excessive addition of lime would significantly suppress the sphalerite. On the one hand, the zinc concentrate was subjected to the flotation test of adding dispersant to assist lime to improve the quality and reduce impurities. On the other hand, the zinc concentrate was subjected to the magnetic separation test. Considering that pyrrhotite is easy to magnetically aggregate and wrap marmatite, sodium hexametaphosphate of polyphosphate and sodium silicate of silicate, which is widely used, were added as dispersants. The results show that the zinc recovery rate is high, basically above 99%, when the zinc concentrate is subjected to magnetic separation with a magnetic field of 0.25T. The zinc grade of the zinc concentrate is 45.77%, and the zinc recovery rate is 99.04%. The addition of dispersant flotation improves the zinc grade of the zinc concentrate, resulting in a large zinc loss rate. Taking all factors into consideration, it is more appropriate to use 0.25T to magnetically separate the zinc concentrate.
[0049] 2.5 Full process closed circuit test The best reagent system, best re-grinding fineness and best magnetic separation field strength of the conditional test were used to conduct a full-process closed-circuit test to examine the separation and recovery of each target mineral in copper-lead concentrate, zinc concentrate, sulfur concentrate, iron concentrate and tailings, and the metal distribution of the ore in each operation. The copper-lead mixed selection operation adopts one roughing selection, two scavenging selections and three concentrating selections to obtain a copper-lead mixed concentrate; the zinc selection operation obtains a zinc concentrate after two roughing selections, three concentrating selections and one scavenging selection, and the zinc concentrate is separated by 025T magnetic separation to obtain a zinc concentrate; the zinc tailings are separated by one roughing selection, one concentrating selection and one scavenging selection to obtain sulfur concentrate 1; the sulfur tailings are separated by magnetic separation to obtain iron rough concentrate and tailings 1, and the iron rough concentrate is re-grinded, and then the desulfurization roughing selection, desulfurization concentrating and one desulfurization scavenging selection are obtained to obtain sulfur concentrate 2 and desulfurized iron concentrate, and the desulfurized iron concentrate is separated by 0.15T magnetic field to obtain the final iron concentrate. The test results are shown in Table 7.
[0050] Table 7 Full process closed circuit test results
[0051] (1) The copper-lead mixed concentrate obtained in the experiment has a lead grade of 60.12%, a copper grade of 0.73%, a copper recovery rate of 33.36%, and a lead recovery rate of 94.72%. The factors affecting the quality of the copper-lead mixed concentrate are mainly pyrite and sphalerite. Since the copper associated grade is extremely low (copper content is 0.045%), and chalcopyrite is often associated with sphalerite, galena, pyrite, and pyrrhotite, the copper recovery rate in the copper-lead mixed concentrate is low, and the copper content in the copper-lead mixed concentrate is only 0.73%. The subsequent copper-lead separation is not economical, so copper-lead separation is not performed; some galena is mainly densely associated with sphalerite, resulting in a copper-lead mixed concentrate zinc grade as high as 6.89%, which can be further studied to improve the lead-zinc separation efficiency.
[0052] (2) The zinc grade of the zinc concentrate was 46.99% and the zinc recovery rate was 88.26%. As part of the chalcopyrite was in fine-grained and milky form and encapsulated in the sphalerite, the copper metal loss in the zinc concentrate was 30.34%.
[0053] (3) Sulfur concentrate 1 and sulfur concentrate 2 were combined into sulfur concentrate, with a sulfur grade of 37.41%, an iron grade of 47.69%, a sulfur recovery rate of 34.57%, and an iron recovery rate of 6.23%. The ratio of pyrite / marcasite in the ore: pyrrhotite = 1:1.76. The theoretical limit sulfur grade of the sulfur concentrate that can be obtained from this ore is 48.38%, and the iron grade is 51.62%. The results show that part of the pyrite / marcasite is lost in the copper-lead mixed concentrate and the zinc concentrate, resulting in a low sulfur grade in the sulfur concentrate.
[0054] (4) Sulfur scavenging 1 After magnetic separation of the tailings, the obtained iron concentrate has an iron grade of 61.00%, a sulfur grade of 0.97%, and an iron recovery rate of 10.79%. In order to obtain high-quality iron concentrate with an iron grade greater than 65% and a sulfur grade less than 0.5%, it is necessary to re-grind the iron concentrate and then flotation desulfurization and magnetic separation to remove impurities.
[0055] (5) The iron recovery rate of the iron concentrate obtained by magnetic separation is 9.33%. Combined with the phase analysis and MLA analysis, it can be seen that the iron in the magnetite accounts for 13.15% of the total iron, indicating that the phase recovery rate of magnetite in the iron concentrate is 70.95%. The iron monomer dissociation degree analysis of the tailings shows that most of the magnetite lost in the tailings is not dissociated, and this part of the magnetite is difficult to recover economically.
[0056] 3 Conclusion (1) The main valuable elements in a polymetallic mine in Qinghai are lead, zinc and iron, with contents of 2.64%, 1.45% and 26.81% respectively. Other associated valuable elements are Au 0.10 g / t, Ag 10.8 g / t, Cu 0.045%, In 55.3 g / t and sulfur 3.94%.
[0057] (2) The ore is composed of 23 minerals in five categories. The independent minerals of copper, lead and zinc are chalcopyrite, galena and sphalerite. There are 12 independent minerals of iron. Iron is mainly found in the form of independent minerals in stylobite, helium-iron pyroxene and magnetite. The distribution rates of iron in them are 46.83%, 16.71% and 13.15% respectively. Only the iron in magnetite has recovery value.
[0058] (3) The ore was processed by a combined flotation magnetic process of copper-lead mixed selection-zinc flotation-sulfur flotation-ferromagnetic selection-iron flotation to obtain a copper-lead mixed concentrate with a lead grade of 60.12%, a copper grade of 0.73%, a copper recovery rate of 33.36%, and a lead recovery rate of 94.72%; a zinc concentrate with a zinc grade of 46.99%, a zinc recovery rate of 88.26%; and an iron concentrate with an iron grade of 67.22% and an iron recovery rate of 9.33%.
[0059] Example 7 Experiments were conducted with the zinc collector GZ-1 prepared in Example 1, Example 2, Example 4 and Example 5, respectively, using the same method as Example 6. The results all showed that the zinc collector GZ-1 described in the present invention is more suitable in the comprehensive recovery process of copper and lead minerals.
Claims
1. A zinc collector GZ-1, characterized in that: The zinc collector GZ-1 is composed of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol.
2. The zinc collector GZ-1 according to claim 1, characterized in that The mass ratio of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol is (0.5-1.5): (0.5-1.5): (0.5-1.5): (0.4-0.6).
3. The zinc collector GZ-1 according to claim 1, characterized in that The mass ratio of isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol is 1:1:1:0.
5.
4. A method for preparing the zinc collector GZ-1 according to any one of claims 1 to 3, characterized in that: The preparation method is obtained by uniformly mixing isobutyl xanthate propylene ester, isobutyl xanthate ethyl formate, isobutyl methyl thiocarbamate and 2-methyl-1-benzyl-2-propanol in a prescribed proportion.
5. An application of the zinc collector GZ-1 according to any one of claims 1 to 3, characterized in that: The zinc collector GZ-1 is used in a multi-metal comprehensive utilization and recovery process.
Citation Information
Patent Citations
Combined capturing and collecting agent
CN101091935A
Collecting agent for copper-zinc flotation separation for copper-zinc ores
CN102806150A
Lead-zinc flotation composite collecting agent and flotation process and application thereof
CN116571355A
Beneficiation method for asynchronous flotation and efficient recovery of high-sulfur copper-lead-zinc-silver-iron polymetallic ore
CN117753550A
Flotation reagent for high-sulfur lead zinc ore in low-alkali environment
CN119327624A